Evolution of external female genital mutilation: why do males harm their mates?. Issue 11 (1st November 2017) - Mouginot, Pierick; Uhl, Gabriele; Fromhage, Lutz
Abstract : Sperm competition may select for male reproductive traits that influence female mating or oviposition rate. These traits may induce fitness costs to the female; however, they may be costly for the males as well as any decrease in female fitness also affects male fitness. Male adaptations to sperm competition manipulate females by altering not only female behaviour or physiology, but also female morphology. In orb-weaving spiders, mating may entail mutilation of external structures of the female genitalia, which prevents genital coupling with subsequent males. Here, we present a game theoretical model showing that external female genital mutilation is favoured even under relatively high costs of mutilation, and that it is favoured by a high number of mate encounters per female and last-male sperm precedence.